ORGANIZATION OF INCLUSIVE SPACE IN THE MODERN UNIVERSITY: INDIVIDUALIZATION AND UNIFICATION - Tymchyk, Olena; Yuliia , Zhukova (Educological discourse, 2021)
The implementation of qualitative inclusion in higher education institutions is one of the conditions for the constant development of Ukraine. The analysis of statistical data, made by the authors, shows a permanent reduce of the number of people with disabilities, who obtain higher education now. Based on the analysis of modern researches and media materials, authors identify the reasons for this tendency. They believe that one of the main barriers is the inability of young people with disabilities to get a job in their specialty and build a successful professional trajectory. Having analyzed the few of Ukrainian universities’ websites, authors propose the development of a unified approach for the special educational services provision. Authors also determine its main elements as: definition of educational difficulties; systematic monitoring of the availability of higher education institutions and of the level of satisfaction of special educational services; expansion of the collected information about students with disabilities; programs of communication ethics among teachers, students and persons with disabilities; psychological services; monitoring the observance of the rights of students with disabilities; inclusion of students with disabilities in academic mobility programs; employment of students with disabilities; determination of quality indicators for the special educational services provision; providing full information on the possibility of provision services to students with disabilities; representation of students with disabilities in the advertising products of institutions – as equal members of the student community. The authors consider these elements as an appropriate base for determination of the quality of higher education institutions inclusion. At the same time, teachers use the individual approach, adjusting a system of «smart adaptation» for students with different physiological and psychological characteristics.